Liverfluke Coprological Cross-Sectional Survey in Cattle, Sheep and Goats in Sharazur District Kurdistan- Iraq - Kwestan Ali; Hardi Marif; Nawroz Kakarash; Hawsar Mohammed (مجلة الانبار للعلوم البيطرية)
Cross-sectional coprological survey was conducted to know the prevalence of liver flukes in cattle, sheep and goats in Sharazur district Kurdistan- Iraq from June 2018 to March 2020. Parasitological examination of fecal samples collected from 685 animals from several field (280 sheep, 245 goats and 160 cattle) was done by using sedimentation method (Fecal Egg Count Reduction Test- FECRT). We revealed that an overall Fasciola species prevalence were (49.48%). Liver fascioliasis was documented highly in sheep (55.71%), followed by cattle (47.5 %) and goats (43.67%). Risk factors such as age and sex showed a significant effects on the prevalence of liver flukes (P<0.05). A higher prevalence rate was noticed and identified in animals older than 3 years old (57.66%) and it was higher than those found in middle age (47.71%) and in young animals (31%). The prevalence of female Fascioliasis was (52.74%) and higher than male Fasciolasis which was (40%).